Prevalence and risk factors of the co‐occurrence of physical frailty and cognitive impairment in Chinese community‐dwelling older adults - Xie, Boqin; Ma, Chenjuan; Chen, Yu; Wang, Junqiao (Health & social care in the community, 2021)
This cross‐sectional study aimed to determine the prevalence of the co‐occurrence of physical frailty and cognitive impairment and to identify its associated demographic, psychosocial and behavioural factors. Participants were recruited from 32 neighbourhoods using multistage sampling method in Xuhui District, Shanghai, China. A total of 1585 older adults were included who lived in community, were 75 years or older and without a clinical diagnosis of dementia. Based on the presences of frailty (using the modified frailty phenotype criteria) and/or cognitive impairment (using Chinese version Mini‐Mental Status Examination stratified by educational level), the participants were classified into four groups: normal, cognitive impairment alone, frailty alone and co‐occurrence. Multinomial logistic regression analyses were conducted to identify the demographic, psychosocial (depression, social participation and social support) and behavioural (sedentary lifestyle and sleep problems) characteristics associated with the co‐occurrence of physical frailty and cognitive impairment. The prevalence of frailty alone, cognitive impairment alone and the co‐occurrence of physical frailty and cognitive impairment in the study sample were 7%, 26.94% and 7.19% respectively. The results of multinomial logistic regression show the following characteristics significantly associated with the co‐occurrence of physical frailty and cognitive impairment: advanced age (81–85 years old, Odds Ratio, OR = 1.99, 95% CI = 1.10–3.59; 86 years or older, OR = 6.43, 95% CI = 3.66–11.29), number of co‐morbidities (OR = 1.34, 95% CI = 1.01–1.77), depression (OR = 3.88, 95% CI = 2.39–6.29), social participation (OR = 0.61, 95% CI = 0.39–0.96), sedentary lifestyle (OR = 2.69, 95% CI = 1.66–4.34) and sleep problems (insomnia occasionally, OR = 1.84, 95% CI = 1.07–3.17; insomnia every day, OR = 2.38, 95% CI = 1.33–4.26). The co‐occurrence of physical frailty and cognitive impairment is a prevalent health issue in oldest old community‐dwelling older adults. Advanced age, co‐morbidity, depression, sedentary lifestyle and sleep problems are risk factors for cognitive frailty while good social participation may have a protective effect on it.